PENGARUH GAME INTERAKTIF WORDWALL TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SEKOLAH DASAR - Fitriani; Muzaini, Muhammad; Jaelani, Abd. Kadir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the use of interactive game learning media Wordwall on the mathematics learning outcomes of fifth-grade students of UPT SDN No. 78 Balang, Takalar Regency. The type of research used is quantitative research with a pre-experimental method using the One Group Pretest-Posttest Design. The population in this study were all fifth-grade students of UPT SDN No. 78 Balang, totaling 37 students, and the entire population was used as a research sample. Data collection techniques were carried out through learning outcome tests (pre-test and post-test) and observation. Data analysis used was descriptive statistical analysis and inferential statistical analysis with paired sample t-test. The results showed that the average pre-test score of students was 60.68 while the average post-test increased to 75.54 after the application of animated video learning media. This increase indicates a change in student learning outcomes after being given treatment in the learning process. The t-test results produced tcount = -19.496 with degrees of freedom (df) = 36 and a significance value (Sig. 2-tailed) = 0.001 < 0.118. This indicates that there is a significant difference between the pre-test and post-test results. Thus, it can be concluded that the use of interactive game learning media Wordwall has a positive and significant effect on improving the Mathematics learning outcomes of fifth-grade students of UPT SDN No. 78 Balang, South Galesong District, Takalar Regency.